2017
DOI: 10.1039/c7nr00758b
|View full text |Cite
|
Sign up to set email alerts
|

Charge stabilizing tris(triphenylamine)-zinc porphyrin–carbon nanotube hybrids: synthesis, characterization and excited state charge transfer studies

Abstract: Functionalization of single-walled (SWCNTs) and double-walled carbon nanotubes (DWCNTs) with a charge stabilizing zinc porphyrin functionalized with triphenylamine entities has been accomplished. The synthetic approach involved the reaction of tris-(triphenylamine)porphyrinato zinc(ii) with iodobenzene functionalized nanotubes through a Sonogashira C-C cross coupling reaction under microwave irradiation conditions. Evidence of covalent functionalization and the extent of functionalization was obtained from sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Functionalization of SWCNTs and DWCNTs with a charge‐stabilizing zinc porphyrin containing triphenylamine moieties has been accomplished by Sonogashira coupling . Free‐radical addition of SWCNTs/DWCNTs with a 4‐iodobenzenediazonium salt (generated in situ from 4‐iodoaniline and isoamyl nitrite) afforded iodophenyl groups on the sidewalls of the CNTs.…”
Section: Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalization of SWCNTs and DWCNTs with a charge‐stabilizing zinc porphyrin containing triphenylamine moieties has been accomplished by Sonogashira coupling . Free‐radical addition of SWCNTs/DWCNTs with a 4‐iodobenzenediazonium salt (generated in situ from 4‐iodoaniline and isoamyl nitrite) afforded iodophenyl groups on the sidewalls of the CNTs.…”
Section: Design and Synthesismentioning
confidence: 99%
“…The CS state of ZnPor–CNT nanohybrids is stabilized by attaching a secondary donor (triphenylamine) to the ZnPor meso positions; femtosecond TA spectra of the hybrids revealed peaks in the 700–740 and 1000–1200 nm ranges where the [(TPA) 4 ZnPor] + absorbance was expected, with the charge‐separated state persisting for ≈1 ns.…”
Section: Intraconjugate Excited‐state Interactionsmentioning
confidence: 99%
“… 1 5 A particularly active area of research is the combination of porphyrins and carbon nanotubes (CNT), which also benefits from the extraordinary physical properties of CNTs. 6 9 Porphyrin–CNT hybrids have been successfully applied to the fabrication of bioinspired high-performance gas sensors, 10 , 11 catalysts, 12 15 model photosynthetic systems, 16 18 and other optoelectronic devices. 19 The physical properties of all these artificial systems depend crucially on the nature of the linker between them.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the surface composition (atom percentages) was evaluated from peak intensities normalized with atomic sensitivity factors, 33 , 34 (see Table S2 in the ESI † ). It was found that the percentage of nitrogen in N-G/C 60 4 decreases with respect to the N-G precursor.…”
Section: Resultsmentioning
confidence: 99%
“…We have successfully used this strategy in the past to demonstrate charge separation and utilization of a charge-separated state in photocatalytic applications in nanocarbon-derived donor–acceptor hybrids. 33 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%